A helyi önkormányzatok és az Alkotmány a pénzügyi jog aspektusából - Csűrös, Gabriella (Debreceni Jogi Műhely, 2006)
In my study I deal with the connection between the local governments and the Constitution in the aspect of Financial Law.The local governments’ essential rights have been laid down  in the Constitution in a separate (IX.) chapter. The defence of the local governments is different from the defence of fundamental human rights. The latter has the test of necessity and proportionality. The local governments’ constitutional rights can be restricted until the infringement of its fundamental contents.I examined the rights of the local governments connected with the Financial Law, so I was engaged mainly in the financial support of it and the right of property and tax assessment. The Constitutional regulation of the financial support is most unique. The difference is that this paragraph (44/A. § (1) c) is not a rule of competence and jurisdiction however an obligation for the state to guarantee the self income and the proper state support to the local governments. The most important own sources are the taxes, which are necessary to discharge the duties. The authority to issue taxes derives from the Constitution - 70/I. § and 44/A. § (1) d. These paragraphs  prescribes that every natural and legal person must contribute to rates and taxes depend on their income and estate.The local governments may issue taxes within the framework of law, but their legislation is wide-ranging within it, for this reason there are a lot of instructive judgements of the Constitutional Court.